Cohort profile: the Turin prostate cancer prognostication (TPCP) cohort - Destefanis, Nicolas; Fiano, Valentina; Milani, Lorenzo; Vasapolli, Paolo; Fiorentino, Michelangelo; Giunchi, Francesca; Lianas, Luca; Del Rio, Mauro; Frexia, Francesca; Pireddu, Luca; Molinaro, Luca; Cassoni, Paola; et al. (Frontiers in Oncology, 2023)
Introduction.Prostate cancer (PCa) is the most frequent tumour among men in Europe and has both indolent and aggressive forms. There are several treatment options, the choice of which depends on multiple factors. To further improve current prognostication models, we established the Turin Prostate Cancer Prognostication (TPCP) cohort, an Italian retrospective biopsy cohort of patients with PCa and long-term follow-up. This work presents this new cohort with its main characteristics and the distributions of some of its core variables, along with its potential contributions to PCa research. Methods.The TPCP cohort includes consecutive nonmetastatic patients with first positive biopsy for PCa performed between 2008 and 2013 at the main hospital in Turin, Italy. The follow-up ended on January 31st 2021. The primary outcome is the occurrence of metastasis; death from PCa and overall mortality are the secondary outcomes. In addition to numerous clinical variables, the study's prognostic variables include histopathologic information assigned by a centralised uropathology review using a digital pathology software system specialised for the study of PCa, tumour DNA methylation in candidate genes, and features extracted from digitised slide images via Deep Neural Networks. Results. The cohort includes 891 patients followed-up for a median time of 10 years. During this period, 97 patients had progression to metastatic disease and 301 died; of these, 56 died from PCa. In total, 65.3% of the cohort has a Gleason score less than or equal to 3+4, and 44.5% has a clinical stage cT1. Consistent with previous studies, age and clinical stage at diagnosis are important prognostic factors: the crude cumulative incidence of metastatic disease during the 14-years of follow-up increases from 9.1% among patients younger than 64 to 16.2% for patients in the age group of 75-84, and from 6.1% for cT1 stage to 27.9% in cT3 stage. Discussion.This study stands to be an important resource for updating existing prognostic models for PCa on an Italian cohort. In addition, the integrated collection of multi-modal data will allow development and/or validation of new models including new histopathological, digital, and molecular markers, with the goal of better directing clinical decisions to manage patients with PCa.